The Morphotectono-Volcanic of Menoreh-Gajah-Ijo Volcanic Rock In Western Side of Yogyakarta-Indonesia - Asmoro Widagdo; Subagyo Pramumijoyo; Agung Harijoko (Journal of Geoscience, Engineering, Environment, and Technology, 2018)
Menoreh-Gajah-Ijo have a very distinctive shape, where there are form of circular structure of volcano that is still intact and the other has not been intact. These morphologies are the morphology of the remaining volcanoes formed by tectonics and certain volcanisms. This study was conducted through a series of interpretations of volcanic body distribution, constructing a Slope Map, constructing a Slope Direction Map, constructing an alignment interpretation on satellite imagery and field mapping work. The formation of Menoreh-Gajah-Ijo morphologies are strongly influenced by tectonics and volcanic processes. The process of tectonism that produces the strike-slip fault structures, the normal faults, and the uplift have formed the lineaments of the valleys and hills with various directions patterns. The Menoreh-Gajah-Ijo volcanisms that have occurred form the structure of volcanic remains. Distribution of Menoreh-Gajah-Ijo volcanic rocks form some semicircle structures because of the normal fault structure that has occurred.